Games in libraries : essays on using play to connect and instruct - Kirsch, Breanne A., 1983- (McFarland & Company, Inc., Publishers, 2014)
"This essay collection discusses innovative uses of games in libraries and focuses on the game making process. The purpose of this book is to bring together distinctive uses of games in libraries or educational institutions and share these ideas with others to inspire the making and use of games by other librarians and educators."--